Method for improving grease and oil resistance of textile products
By applying a composition of anionic and cationic polymers with specific charge densities to cellulose fibers, the method enhances the grease and oil resistance of molded textile products, addressing the inadequacies of current technologies and improving their performance and sustainability.
Patent Information
- Application Number
- JP2024536991
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-22
- Filing Date
- 2022-12-01
- Publication Date
- 2025-01-17
AI Technical Summary
Current textile technologies are not suitable for use as lids for containers of meat and poultry, prepared foods, microwaveable foods, and beverages due to inadequate grease and oil resistance, and existing molded pulp packaging lacks the necessary barrier properties.
A method involving the use of a composition comprising anionic and cationic polymers with specific charge densities, combined with polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, or starch, is applied to cellulose fibers to enhance grease and oil resistance in molded textile products.
The composition significantly improves the oil and grease resistance of molded textile products, increasing penetration time and reducing thickness and mass per unit area, while maintaining biodegradability and compostability.
Smart Images

Figure 2025501088000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates generally to a method for improving the grease and oil resistance of textile products, and more particularly, but not by way of limitation, to a method for improving the grease and oil resistance of textile products by shaping textile raw materials.
[0002] Please note that this section provides useful background information, but is not an admission that the technology described herein represents the state of the art.
[0003] Pollution from single-use plastic packaging and materials is widespread, marring the world's landscapes and threatening delicate ecosystems and the life forms that inhabit them. Single-use packaging travels through waterways and into oceans in the form of Styrofoam and Expanded Polystyrene (EPS) packaging, take-out containers, bottles, thin film bags, photodegradable plastic pellets, and more. Sustainable solutions to reduce plastic pollution are gaining momentum. However, sustained adoption requires that these solutions are not only environmentally good, but also competitive in both performance and cost with fossil-fuel-based plastics.
[0004] To provide some brief background, molded paper pulp products (fiber molded products) have been used for packaging such as containers and trays since the 1930s, but declined in the 1970s with the advent of fossil fuel-based foamed plastic packaging. Paper pulp can be produced from old newspapers, cardboard boxes, and other plant fibers. Today, molded pulp packaging is widely used for electronics, household goods, auto parts, and medical products, and is also used as edge / corner protectors and pallet trays when transporting electronic and other fragile parts.
[0005] Cellulosic fiber-based packaging products are biodegradable and compostable and, unlike fossil-fuel-based plastics, do not migrate into the ocean. However, currently known fiber technologies are not suitable for use as closures for meat and poultry, cooked or prepared foods, microwaveable foods, or beverages such as hot coffee.
[0006] Depending on the application of the molded pulp, barrier properties against oil, grease, water, water vapor, oxygen and / or other gases and liquids are required for various product types. The use of appropriate slurry chemistry can result in improved process efficiency, mechanical properties, barrier properties and / or surface coatability, making the production of molded pulp products more competitive with those made from flat boards. Abstract
[0007] According to a first aspect, the present invention provides a method for improving the grease and oil resistance of a molded textile product, the method comprising: Obtaining a fiber stock comprising cellulosic fibers; introducing a composition into said fiber material; wherein the composition comprises at least one anionic polymer having a molecular weight of at least 100 kDa; · cationic polymers; wherein the anionic polymer and the cationic polymer have a molecular weight of at least 100 kDa and impart a charge density to the composition in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and impart a charge density to the composition in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured as an aqueous solution at pH 7.0; In some embodiments, the method includes introducing polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fiber raw material; forming the fiber material; Includes.
[0008] According to a second aspect, the invention provides a molded fiber product comprising a composition comprising: at least one anionic polymer having a molecular weight of at least 100 kDa; · cationic polymers; wherein the anionic polymer and the cationic polymer have a molecular weight of at least 100 kDa and impart a charge density to the composition in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and impart a charge density to the composition in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured as an aqueous solution at pH 7.0; In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; In some embodiments, a pigment; wherein said shaped textile product is produced by a method according to the invention.
[0009] According to a third aspect, the present invention provides the use of a composition comprising: at least one anionic polymer having a molecular weight of at least 100 kDa; · cationic polymers; wherein the anionic polymer and the cationic polymer have a molecular weight of at least 100 kDa and impart a charge density to the composition in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and impart a charge density to the composition in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured as an aqueous solution at pH 7.0; In some embodiments, the composition comprises polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or a mixture thereof; Some embodiments include pigments to improve the grease and oil resistance of the molded fiber.
[0010] It has now been found that molded textiles (e.g., thermoformed textiles) containing a composition comprising at least one anionic polymer having a molecular weight of at least 100 kDa and a cationic polymer, the composition having a particular charge density, surprisingly have excellent oil resistance. Surprisingly, it has been found that the composition acts as an oil barrier in the textile. It is also believed that the composition acts as a grease barrier in the textile.
[0011] The composition has been found to exhibit excellent oil resistance with respect to olive oil, i.e., the composition has been found to increase the penetration time of molded textiles by about 60 minutes compared to molded textiles not containing the composition. It is also believed that grease resistance in terms of penetration time and / or uptake of grease is increased as well as oil uptake.
[0012] It has also been surprisingly found that molded fiber products comprising this composition and polyamidoamine epichlorohydrin (PAAE), glyoxalated polyacrylamide, starch, or mixtures thereof, have better oil resistance and are believed to have better grease resistance.
[0013] It has been found that the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, when combined with the above composition, provides improved oil resistance compared to molded textiles without the use of the above composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, or mixtures thereof. That is, the penetration time and uptake into molded textiles (e.g., thermoformed textiles) is found to increase by about 200 minutes. It is also believed that grease resistance is improved.
[0014] It is believed that molded textile products containing a composition including an anionic component and a cationic component capture, i.e., take in, or absorb / adsorb grease and oil components and act as a grease barrier and an oil barrier. Without being bound by any theory in this regard,
[0015] The textile products of the present invention are at least partially biodegradable and compostable, preferably mostly biodegradable and compostable, and more preferably biodegradable and compostable.
[0016] It has also been surprisingly found that a textile product with oil and / or grease resistance can be produced in a simple and low-cost manner. It has been found that a textile product with grease and / or oil resistance can be produced by introducing a textile raw material containing a composition with a specific charge density, the composition comprising at least one anionic polymer and a cationic polymer, into a textile raw material containing cellulosic fibers, and molding (e.g., thermoforming) the textile raw material. In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or a mixture thereof is introduced before molding.
[0017] Surprisingly, it has been found that by incorporating the composition in large amounts (e.g., 5-50 kg / t based on the dry weight of the fiber raw material) into the fiber raw material, the molded articles produced have high oil resistance. The oil resistance is further increased by additionally incorporating polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof into the fiber raw material. It is also believed that the grease resistance is improved.
[0018] It has also been surprisingly found that the molded textiles described above (e.g., thermoformed textiles) have improved tensile bending stiffness compared to molded textiles that do not include the composition, or the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof. The improved tensile bending stiffness allows the thickness of the molded textile to be reduced, thereby allowing the mass per unit area of the molded textile to be reduced.
[0019] Since the thickness and mass per unit area can be reduced, the weight of the textile product can be reduced, and therefore the cost of textile raw materials can be reduced.
[0020] It is also believed that the addition of the composition, or the composition together with polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fiber raw materials in the board manufacturing process will impart grease and oil resistance to the board.
[0021] It has also been found that the addition of pigments and / or other additives to the composition prior to igniting the composition on the textile raw materials improves the gloss, smoothness, coatability and / or barrier properties of the molded textile product. The appended claims define the scope of protection. [Brief description of the drawings]
[0022] [Figure 1] Olive oil resistance at 40℃ for 500g / m2 or 400g / m2 hot-press dried two-dimensional fiber molded products. The properties of several fiber molded products with different chemical properties of fiber raw materials are shown. [Diagram 2] The dry tensile properties of a 500g / m2 hot-press dried 2D fiber molded product are shown. The properties of several fiber molded products with different chemical properties of the fiber raw materials are shown. [Diagram 3]High moisture tensile properties of 500g / m2 hot press dried 2D fiber molded product. Properties of several fiber molded products with different chemical properties of fiber raw materials are shown. [Figure 4] Olive oil resistance at 40℃ of a 400g / m2 hot-press dried 2D fiber molded product. The properties of several fiber molded products with different chemical properties of the fiber raw materials are shown. [Diagram 5] Dry tensile properties of a 400 g / m2 hot-press dried 2D fiber molded product are shown. The properties of several fiber molded products with different chemical properties of the fiber raw materials are shown. [Figure 6] This refers to a vacuum-formed two-dimensional textile product or textile sheet. [Figure 7] It is a molded three-dimensional textile product. Detailed explanation
[0023] According to a first aspect, the present invention provides a method for improving the grease and oil resistance of a molded textile product, the method comprising: Obtaining a fiber raw material comprising cellulosic fibers; introducing a composition into said fiber material; wherein the composition comprises at least one anionic polymer having a molecular weight of at least 100 kDa; · cationic polymers; wherein the anionic polymer and the cationic polymer have a molecular weight of at least 100 kDa and impart a charge density to the composition in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and impart a charge density to the composition in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured as an aqueous solution at pH 7.0; In some embodiments, the method includes introducing polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fiber raw material; forming the fiber material; Includes.
[0024] The anionic polymer and the cationic polymer of the composition provide a charge density to the composition.
[0025] In some embodiments, polyamidoamine epichlorohydrin (PAAE), glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fiber raw material. Preferably, polyamidoamine epichlorohydrin is introduced into the fiber raw material.
[0026] In some embodiments, a pigment is introduced to the fiber raw material. In some embodiments, the pigment is introduced to the fiber raw material before the composition is added to the fiber raw material. In some embodiments, the pigment is introduced to the fiber raw material after the composition is added to the fiber raw material. In some embodiments, the pigment is introduced to the fiber raw material at the same time as the composition is added to the fiber raw material. In some embodiments, the pigment and the composition are introduced to the fiber raw material as a mixture.
[0027] In some embodiments, the pigment comprises talc, kaolin clay, calcium carbonate, or mixtures thereof.
[0028] The molding, i.e., molding step or process, can be any suitable method known in the art.
[0029] In some embodiments, forming includes wet forming, wet forming, vacuum forming, vacuum forming, extrusion forming, extrusion molding, thermoforming, dry forming, dry forming, heat pressing, heat press drying, thermoforming, heat pressing, thermoforming, thermoforming, or combinations thereof, preferably thermoforming, more preferably heat pressing, heat press drying or thermoforming.
[0030] In some embodiments, the fiber material is formed into a sheet.
[0031] In some embodiments, the fibrous material is formed into a sheet, preferably by thermoforming into a sheet.
[0032] The fibrous material can be thermoformed into a sheet by any suitable method known in the art, such as a heat press in which mechanical pressure and high temperature are applied between two metal plates that sandwich the fibrous material.
[0033] As used herein, the term "sheet" means an article having a thickness that is less than its length and width.
[0034] In this application, the term "two-dimensional product" refers to a two-dimensional product that is originally made into a flat shape and has a thickness that is less than its length and width. The two-dimensional product can be folded, bent, formed, or molded into a three-dimensional product.
[0035] As used herein, the terms "three-dimensional product" and "3D product" refer to a product that has three dimensions. Sheets are not considered to be three-dimensional products as used herein.
[0036] In some embodiments, the sheet is formed into a three-dimensional article.
[0037] In some embodiments, the fibrous material is formed into a three-dimensional article.
[0038] In some embodiments, the fiber raw material is formed into a two-dimensional sheet having a thickness of 0.1 mm to 10 mm, preferably 0.3 mm to 2 mm. In some embodiments, the 2D sheet is further thermoformed (i.e. dry formed) into a three-dimensional product, preferably having a length and width of 5 cm to 50 cm, a depth of 2 cm to 20 cm, and a wall thickness of 0.1 mm to 2 mm.
[0039] In some embodiments, the fibrous raw material with or without foam is vacuum formed or extruded, wet pressed and / or drained with the aid of vacuum, dried unconstrained and / or constrained, compressed in one or more directions, polymer impregnated, polymer laminated, polymer coated or a combination thereof into a two-dimensional sheet having a thickness of 0.1 mm to 10 mm, preferably 0.3 mm to 2 mm. In some embodiments, the 2D sheet is further thermoformed (i.e. dry formed) into a three-dimensional product, preferably having a length and width of 5 cm to 50 cm, a depth of 2 cm to 20 cm and a wall thickness of 0.1 mm to 2 mm.
[0040] In some embodiments, the fibrous material is wet shaped and the wet shaped fibrous material is formed into a three-dimensional article.
[0041] In some embodiments, the fibrous raw material is vacuum formed or wet molded into a three dimensional product, preferably with length and width of 5 cm to 50 cm and depth of 2 cm to 20 cm, and then thermoformed and dried to a wall thickness of preferably 0.1 mm to 3 mm, more preferably 0.3 mm to 1.0 mm.
[0042] Depending on the embodiment, the temperature of the mold in the heat press, hot press, hot press drying, thermoforming or thermoforming is 100°C to 400°C, preferably 130°C to 200°C.
[0043] In some embodiments, the mechanical pressure applied to the fiber raw material or the two-dimensional or three-dimensional fiber product during heat pressing, hot pressing, hot press drying or thermoforming is between 0.1 bar and 1000 bar, preferably up to 20 bar, and depending on the production technique, the equipment and the application of the fiber molded product, the pressure may vary during heat pressing, hot pressing, hot press drying or thermoforming.
[0044] In some embodiments, the shaping is shaping into a three-dimensional article, including thermoforming, heat pressing, thermoforming, wet or dry forming, and / or wet or dry forming, densification, or combinations thereof.
[0045] In some embodiments, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof and the composition are introduced sequentially to the fiber raw material. Preferably, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced to the fiber raw material prior to introducing the composition to the fiber raw material.
[0046] In some embodiments, the composition is introduced into a fiber raw material, followed by introduction of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof into the fiber raw material.
[0047] In some embodiments, at least one anionic polymer and a cationic polymer are sequentially introduced into the fiber raw material. Preferably, the at least one cationic polymer is introduced into the fiber raw material before the anionic polymer is introduced into the fiber raw material.
[0048] In some embodiments, the anionic polymer is introduced into the fiber raw material prior to the introduction of the at least one cationic polymer.
[0049] In some embodiments, the at least one anionic polymer, the cationic polymer, and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced sequentially to the fiber raw material.
[0050] In some embodiments, the at least one anionic polymer and the cationic polymer are introduced sequentially into the fiber raw material, followed by the introduction of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof into the fiber raw material.
[0051] In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to a fiber raw material, followed by sequentially introducing the at least one anionic polymer and the cationic polymer to the fiber raw material.
[0052] In some embodiments, the at least one anionic polymer is introduced to a fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, and then the cationic polymer is introduced to the fiber raw material.
[0053] In some embodiments, the cationic polymer is introduced into a fiber raw material, followed by introduction of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, into the fiber raw material, and then introduction of the at least one anionic polymer into the fiber raw material.
[0054] The composition comprises a mixture of anionic and cationic polymers. The anionic and cationic polymers may be mixed before adding the composition as an aqueous solution to the fiber raw material, i.e. before adding as a single solution. The mixing may be performed by any suitable method of mixing the anionic and cationic polymers. For example, the anionic and cationic polymers may be mixed in dry form or as an aqueous solution. Alternatively, the anionic or cationic polymer in dry form may be dissolved in an aqueous solution with the other component.
[0055] In some embodiments, the composition is in the form of an aqueous solution and is introduced to the fiber raw material as an aqueous mixture. The term "aqueous solution" as used herein includes true solutions as well as suspensions and emulsions. Preferably, the composition in the form of an aqueous solution contains only small amounts of undissolved residue or no undissolved residue or solids.
[0056] In some embodiments, the composition may be in the form of a dry particulate material. In this case, the risk of the composition deteriorating during transportation or storage is reduced, improving the shelf life. In particular, cationic starch as a cationic polymer is vulnerable to microbiological degradation and will lose its performance if decomposed. The composition may preferably be a mixture of a solid particulate anionic polymer and a solid particulate cationic polymer. Such a particulate mixture is easy to store and transport, and is economically advantageous. The moisture content of the composition in the form of a dry particulate material should be at most 25% by weight. The particle size of the dry particulate material may vary, for example, between 5 and 2000 microns.
[0057] If the composition is in the form of dry particulate matter, it can be dissolved in water to obtain an aqueous composition, which may be done using effective high shear dissolving means, such as a rotor / stator mixer, in some embodiments by applying heat, in some embodiments by using a jet cooker. The dissolving may be done, for example, at the work site. According to a preferred embodiment, the composition in the form of dry particulate matter is dissolved in water, preferably using high shear dissolving means, to obtain an aqueous composition. In some embodiments, the aqueous composition obtained may then be diluted and then introduced into the fiber raw material.
[0058] In some embodiments, an amphoteric polymer having both anionic and cationic groups is introduced into the fiber material, preferably in place of the composition. The amphoteric polymer provides a charge density of 0.1 to 1.5 meq / g when measured at pH 2.8, and a charge density of -0.1 to -3 meq / g, preferably -0.3 to -2.5 meq / g, more preferably -0.5 to -2.0 meq / g when measured at pH 7.0.
[0059] In some embodiments, an IPN (Interpenetrating Polymer Network) material having both anionic and cationic groups is introduced into the fiber raw material, preferably instead of the composition, which provides a charge density of 0.1 to 1.5 meq / g when measured at pH 2.8, and a charge density of -0.1 to -3 meq / g, preferably -0.3 to -2.5 meq / g, more preferably -0.5 to -2.0 meq / g when measured at pH 7.0.
[0060] In some embodiments, a polymer having both anionic and cationic groups, preferably an amphoteric polymer and / or an interpenetrating polymer network material, is introduced into the fiber raw material, preferably instead of the composition, where the amphoteric polymer and / or the interpenetrating polymer network material provides the charge density described above.
[0061] In some embodiments, the composition is introduced in an amount of 5-50 kg / t, preferably 10-40 kg / t, more preferably 20-30 kg / t, based on the dry weight of the fibre raw material.
[0062] In some embodiments, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide or mixtures thereof are introduced in an amount of 1 kg / t to 8 kg / t, preferably 2 kg / t to 6 kg / t, more preferably 2 kg / t to 4 kg / t, dry weight based on the dry weight of the fiber raw material.
[0063] In some embodiments, the starch comprises native starch, cooked starch, uncooked starch, cationic starch, native chemically modified starch, physically modified polymer-grafted starch, enzyme modified starch, anionic starch, amphoteric starch, crosslinked starch, pregelatinized starch, swelling starch, or granular starch, or mixtures thereof.
[0064] In some embodiments, the starch is introduced in an amount of from 1 kg / t to 100 kg / t dry weight, based on the dry weight of the fiber raw material.
[0065] In some embodiments, the cationic starch is introduced in an amount of from 1 kg / t to 20 kg / t dry weight, based on the dry weight of the fiber raw material.
[0066] In some embodiments, the non-ionic starch is introduced in an amount of from 1 kg / t to 100 kg / t dry weight, based on the dry weight of the fiber raw material.
[0067] In some embodiments, the pH of the fiber raw material is adjusted to a pH value of 5 to 9, preferably 7 to 8, prior to introducing the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof into the fiber raw material.
[0068] In some embodiments, the electrical conductivity of the fiber material is adjusted to between 0.05 mS / cm and 6 mS / cm, preferably between 0.1 mS / cm and 1 mS / cm, prior to the introduction of the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof to the fiber material. In some embodiments, the electrical conductivity is adjusted with a material consisting of 70% calcium acetate, 20% sodium sulfate, and 10% sodium bicarbonate.
[0069] In some embodiments, a sizing chemical, fixing agent, wet strength agent, drainage aid, or mixtures thereof is introduced to the fibrous material after or before the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to the fibrous material.
[0070] In some embodiments, a sizing agent, fixing agent, wet strength agent, drainage aid, or mixtures thereof is introduced to the fibrous raw material prior to introducing the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof to the fibrous raw material.
[0071] In some embodiments, the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to a fiber raw material prior to introducing a sizing agent, fixing agent, wet strength agent, drainage aid, or mixtures thereof to the fiber raw material.
[0072] In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are introduced to the fibrous raw material prior to introducing the sizing agent to the fibrous raw material.
[0073] In some embodiments, the sizing agent and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are simultaneously but separately introduced to the fibrous raw material.
[0074] In some embodiments, the sizing agent and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, or mixtures thereof are introduced as a mixture to the fiber raw material.
[0075] In some embodiments, the sizing agent comprises an alkyl ketene dimer (AKD), an alkenyl succinic anhydride (ASA), rosin, or a mixture thereof.
[0076] In some embodiments, the AKD, ASA, rosin or mixtures thereof, and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced as a mixture to the fiber raw material, preferably before the composition is introduced to the fiber raw material.
[0077] In some embodiments, the AKD, ASA, rosin or mixtures thereof, and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced as a mixture to the fiber raw material, preferably after the composition is introduced to the fiber raw material.
[0078] In some embodiments, the AKD, ASA, rosin, polyamidoamine epichlorohydrin, glyoxalate polyacrylamide, starch, or mixtures thereof are introduced to the fiber raw material as a mixture, preferably prior to introducing the composition to the fiber raw material.
[0079] In some embodiments, the AKD, ASA, rosin, polyamidoamine epichlorohydrin, glyoxalate polyacrylamide, starch, or mixtures thereof are introduced to the fiber raw material as a mixture, preferably after the composition is introduced to the fiber raw material.
[0080] In some embodiments, the AKD, ASA, rosin or mixtures thereof are incorporated in an amount of 0.1-4%, preferably 0.5-1.5%, based on the dry weight of the fiber material.
[0081] In some embodiments, the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide or mixtures thereof are introduced in an amount of 1-8 kg / t dry weight, preferably 2-4 kg / t dry weight, based on the dry weight of the fiber raw material.
[0082] In some embodiments, the fixing agent, the drainage aid, or a mixture thereof comprises aluminum sulfate (ALS), polyaluminum chloride (PAC), poly(diallyldimethylammonium chloride) (PDACMAC), cationic polyacrylamide (CPAM), or a mixture thereof.
[0083] In some embodiments, the wet strength agent comprises polyamide epichlorohydrin (PAE), glyoxalated polyacrylamide (GPAM), starch, or mixtures thereof. In some embodiments, the wet strength agent is added after the addition of a sizing agent, but before the composition is added to a fiber raw material.
[0084] In some embodiments, a fiber material is obtained that comprises cellulosic fibers, the fiber material having a consistency of 0.1%-10%, preferably 0.2%-1.0%, more preferably 0.2%-0.5%.
[0085] In some embodiments, the fiber raw materials comprising cellulosic fibers include natural fibers, synthetic fibers, or mixtures thereof. The fibers are preferably plant-based fibers, including recycled, chemical and / or mechanical hardwood and softwood pulp, sugarcane (such as bagasse), bamboo, barley, wheat, corn, oat, rice, rye, tomato, sorghum, rapeseed, palm oil plants, flax, hemp, ramie, cotton, kenaf, jute, banana, hemp, peat, sphagnum moss, or mixtures thereof.
[0086] In some embodiments, the anionic polymer has a molecular weight of at least 100 kDa, preferably at least 300, more preferably from 100 kDa to 10,000 kDa, even more preferably from 100 kDa to 700 kDa, even more preferably from 100 kDa to 600 kDa.
[0087] In some embodiments, the anionic polymer comprises carboxymethylcellulose, microfibrillated cellulose, microfibrillated lignocellulose, anionic starch, chitosan, pectin, fatty acid esters, other anionic and anionic derivatized polysaccharides or mixtures thereof, preferably anionic starch, carboxymethylcellulose, microfibrillated cellulose, microfibrillated lignocellulose or mixtures thereof.
[0088] In some embodiments, the cationic polymer comprises a starch derivative such as hydroxypropylated starch, nanocellulose, microfibrillated cellulose, lignocellulose-based derivatives, chitosan, alpha glucan, polyhydroxyalkanoates, polylactic acid, cationic starch or mixtures thereof, preferably cationic starch, chitosan, nanocellulose, microfibrillated cellulose, lignocellulose-based derivatives or mixtures thereof.
[0089] As is known, polysaccharides are natural polymers formed from macromolecular carbohydrate molecules, which contain long chains of monosaccharide units as repeating units linked by covalent bonds. Polysaccharides are extracted from various plant sources, microorganisms, etc. The polysaccharide chains contain multiple hydroxyl groups capable of hydrogen bonding.
[0090] As used herein, the term "anionically derivatized" is understood to mean not only chemical modification of a polysaccharide by a reaction resulting in anionic groups covalently attached in the polysaccharide structure, but also sufficient association of the anionic groups with the polysaccharide structure to impart the composition with desired properties, such as charge density. Such sufficient association of the anionic groups can be achieved, for example, by adsorption. Alternatively, it can be achieved by other treatments of the polysaccharide starting material, such as mechanical treatment. It is also possible to obtain anionically derivatized polysaccharides (anionically derivatized polysaccharides) by combining other treatments, such as mechanical processing, with chemical modification. Chemical modification of polysaccharides is preferred to provide anionically derivatized polysaccharides suitable for use in the present invention. Anionic groups may be provided, for example, by incorporating carboxyl groups, sulfate groups, sulfonate groups, phosphonate groups, phosphate groups (including their salt forms), or combinations thereof, into the polysaccharide structure. Anionic groups may be introduced into the polysaccharide structure by suitable chemical modifications, such as carboxymethylation, oxidation, sulfation, sulfonation, phosphorylation, etc.
[0091] In some embodiments, anionically derivatized polysaccharides suitable for use in the present invention may have charge density values in the range of -0.05 to 5.0 meq / g, measured at pH 7. For example, they may have charge density values in the range of -0.3 to 5.0 meq / g or -0.5 to 5.0 meq / g, preferably -0.7 to 4.5 meq / g, more preferably -1.0 to 4.0 meq / g. The measured charge density values are calculated per dry weight.
[0092] The anionically derivatized polysaccharide may comprise a water-soluble and / or a suspendable anionically derivatized polysaccharide. As used herein, an aqueous solution of an anionically derivatized polysaccharide includes not only a true solution but also a suspension of an anionically derivatized polysaccharide. Preferably, the anionically derivatized polysaccharide is water-soluble and contains at most 30% by weight, preferably at most 20% by weight, more preferably at most 15% by weight, and even more preferably at most 10% by weight of water-insoluble material. Water solubility can improve the availability of functional groups on the polysaccharide, thereby improving the interaction with cationic polymers, such as cationic starch, of the composition, and other components present in the fiber raw material.
[0093] In some embodiments, the anionically derivatized polysaccharide comprises an anionically derivatized cellulose, an anionically derivatized starch, or a combination thereof, including modified celluloses and starches such as hydroxyethyl cellulose, e.g., hydroxyethyl starch, ethyl hydroxyethyl cellulose, ethyl hydroxyethyl starch, hydroxypropyl cellulose, hydroxypropyl starch, hydroxypropyl hydroxyethyl cellulose, hydroxypropyl hydroxyethyl starch, methyl cellulose, methyl starch, and the like.
[0094] In some embodiments, the anionically derivatized polysaccharide comprises cellulose, preferably carboxymethylated cellulose, more preferably carboxymethyl cellulose. The anionically derivatized polysaccharide may comprise, for example, purified carboxymethyl cellulose or technical grade carboxymethyl cellulose. Carboxymethyl cellulose may be produced by any process known in the art. When the composition comprises an anionically derivatized polysaccharide comprising cellulose, it is believed that the backbone structure of the polysaccharide is similar to that of cellulosic fibers in pulp, i.e., that exhibit 1,4-β glycosidic bonds in the backbone. This matching structure may result in stronger interactions between the composition and the fibers.
[0095] In some embodiments, the anionically derivatized polysaccharide comprises a carboxymethylated cellulose, preferably a carboxymethyl cellulose, having a degree of carboxymethyl substitution of 0.2 or more, preferably 0.3 to 1.2, more preferably 0.4 to 1.0 or 0.5 to 1.0, which further enhances water solubility. In some preferred embodiments, the carboxymethylated cellulose can have a degree of carboxymethyl substitution in the range of 0.5 to 0.9, which provides the carboxymethylated cellulose with essentially complete water solubility.
[0096] In some embodiments, the anionically derivatized polysaccharide comprises a carboxymethylated cellulose, preferably a carboxymethyl cellulose, which may have a charge density of less than -1.1 meq / g, preferably between -1.6 and -4.7 meq / g, more preferably between -2.1 and -4.1 meq / g, and even more preferably between -2.5 and -3.8 meq / g, measured at pH 7. All charge density values measured are calculated on a dry weight basis.
[0097] In some embodiments, the anionically derivatized polysaccharide comprises a carboxymethylated cellulose, preferably a carboxymethyl cellulose, which may have a viscosity in the range of 100-30,000 mPas, preferably 200-20,000 mPas, more preferably 500-10,000 mPas, measured from a 2% by weight aqueous solution at 25° C. using a Brookfield LVDV1.
[0098] In some embodiments, the anionically derivatized polysaccharide comprises carboxymethylated cellulose, preferably carboxymethyl cellulose.
[0099] In some embodiments, the anionically derivatized polysaccharide is at least partially microfibrillar.
[0100] Preferably, the anion-derivatized polysaccharide comprises anionic microfibril cellulose. Although microfibril cellulose is sometimes called nanocellulose, as used herein, microfibril cellulose or nanocellulose does not refer to crystalline cellulose derivatives, such as those known as microcrystalline cellulose (MCC), nanocrystalline cellulose (NCC), or cellulose nanowhiskers. In other words, crystalline cellulose derivatives are excluded from anionic microfibril cellulose. Or their microfibrils may have an average diameter of 2 to 60 nm, preferably 4 to 50 nm, more preferably 5 to 40 nm, and an average length of a few μm, preferably 500 μm or less, more preferably 300 μm or less, more preferably 2 to 200 μm, even more preferably 10 to 100 μm, and most preferably 10 to 60 μm. Microfibrillated cellulose often comprises bundles of 10 to 50 microfibrils.
[0101] In some embodiments, the anionically derivatized polysaccharide does not include microfibril cellulose.
[0102] In some embodiments, the composition comprises a cationic starch of natural origin and has an amylopectin content of at least 80% by weight. Amylopectin is a branched starch molecule. Branching usually occurs at α(1→6) linkages, with every 15-30 anhydroglucose units of the starch backbone containing α(1→4) linkages. The amylopectin content of the cationic starch ensures that the size of the polyion complexes formed has the appropriate dimensions required for good oil resistance.
[0103] In some embodiments, the cationic starch of the composition may have an amylopectin content of 85% by weight or more, preferably 90% by weight or more, more preferably 95% by weight or more. The cationic starch of the composition may be derived from potato, waxy potato, rice, waxy corn, sweet potato, arrowroot or tapioca starch, or any combination thereof. Preferably, the cationic starch is derived from waxy corn starch and / or waxy potato starch.
[0104] Cationic starch comprises starch units, i.e. starch molecules, of which at least 70% by weight, preferably at least 80% by weight, more preferably at least 85% by weight, even more preferably at least 90% by weight, and in some cases even more preferably at least 95% by weight, have an average molecular weight MW of more than 20 million000000 g / mol, preferably 50 million00000 g / mol or more, more preferably 100 million00000 g / mol or more, in some cases 200 million00000 g / mol or more, such as from 200 million00000 g / mol to 500 million00000 g / mol.
[0105] In some embodiments, the composition comprises a cationic starch, which comprises a cationic unfloured starch. The cationic unfloured starch provides optimal interaction with the anion-derivatized polysaccharide and other components of the fiber raw material, such as fibers and / or inorganic fillers. As used herein, the term "unfloured starch" refers to starch that has not been essentially treated by oxidative, thermal, enzymatic and / or acidic treatments that cause hydrolysis of glycosidic bonds or degradation of starch molecules or starch units. When starch is solubilized by cooking, the cooking temperature is less than 140°C, preferably less than 120°C, and often less than 110°C or less than 105°C.
[0106] For example, the unfloured cationic starch after solubilization has a viscosity that is at least 20%, preferably at least 50%, of the viscosity of the corresponding native starch solubilized by heating for 30 minutes at 97° C. Viscosity measurements are performed using a Brookfield LV-DVI viscometer at 2% solids and room temperature.
[0107] Cationic starch suitable for use in the composition can be obtained by cationizing starch by any suitable method.Preferably, cationic starch is obtained by using (3-chloro-2-hydroxypropyl)trimethylammonium chloride or (2,3-epoxypropyl)trimethylammonium chloride.It is also possible to cationize starch using cationic acrylamide derivatives such as (3-acrylamidopropyl)trimethylammonium chloride.Various methods for cationizing starch are known to those skilled in the art.
[0108] In some embodiments, cationic starch is one that has been obtained using cationization as the only chemical derivatization of the starch, and thus the cationic starch is non-crosslinked, non-grafted, or otherwise chemically modified.
[0109] The cationic starch of the composition may have a degree of substitution of 0.025-0.3, preferably 0.03-0.16, more preferably 0.045-0.1. The degree of substitution is relative to the degree of cationization of the starch, with a higher degree of substitution indicating a higher degree of cationization. Cationic starches with a relatively high degree of substitution and cationization may provide additional benefits and are therefore preferred for use in the composition.
[0110] In one preferred embodiment, the composition does not include a synthetic cationic polymer.
[0111] In some embodiments, the compositions, cationic starches and / or anionic derivatized polysaccharides may further comprise adjuvants or additives, such as preservatives, biocides, stabilizers, antioxidants, pH adjusters, and the like.
[0112] In some embodiments, the composition comprises an anionically derivatized polysaccharide and cationic starch in a (dry) weight ratio of from 10:90 to 90:10, preferably from 30:70 to 70:30. Weight ratios are given as dry weights. Preferably, the weight ratio of anionically derivatized polysaccharide and cationic starch is selected such that the composition is net anionic at the pH of the fiber raw material.
[0113] According to a second aspect, the invention provides a molded fiber product comprising a composition comprising: at least one anionic polymer having a molecular weight of at least 100 kDa; · cationic polymers; wherein the anionic polymer and the cationic polymer have a molecular weight of at least 100 kDa and impart a charge density to the composition in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and impart a charge density to the composition in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured as an aqueous solution at pH 7.0; In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; In some embodiments, a pigment; wherein said shaped textile product is produced by a method according to the invention.
[0114] In some embodiments, the molded fiber comprises polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof.
[0115] In some embodiments, the molded fiber product comprises a pigment.
[0116] In some embodiments, the molded textile is a thermoformed textile, preferably a heat pressed, heat press dried, heat pressed textile or a thermoformed textile.
[0117] In some embodiments, the amount of fiber in the molded fiber product is 50wt.%-99wt.%, preferably 70wt.%-97wt.%, more preferably 90wt.%-97wt.%, based on the dry weight of the molded fiber product.
[0118] In some embodiments, the amount of the composition in the molded fiber product is from 0.5 wt.% to 10 wt.%, preferably from 1 wt.% to 3 wt.%, based on the dry weight of the molded fiber product.
[0119] In some embodiments, the amount of polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof in the molded fiber product is from 0.05 wt.% to 0.8 wt.%, preferably from 0.2 wt.% to 0.4 wt.%, based on the dry weight of the molded fiber product.
[0120] In some embodiments, the amount of pigment in the molded textile product is from 0.01 wt.% to 5 wt.%, preferably from 0.5 wt.% to 4 wt.%, based on the dry weight of the molded textile product.
[0121] In some embodiments, the molded textile product comprises a sizing agent, a fixing agent, a wet strength agent, a drainage aid, or mixtures thereof. In some embodiments, the amount of sizing agent, fixing agent, or mixtures thereof in the molded textile product is between 0.1 wt.% and 5 wt.%, preferably between 0.5 wt.% and 2.5 wt.%, based on the dry weight of the molded textile product.
[0122] In some embodiments, the shaped fiber product comprises a food package, a food service article, a beverage package, a beverage service article, a merchandise package, or a merchandise service article, preferably a food service or packaging article such as an ovenable tray, a microwaveable tray, a clamshell box, other food boxes, soup cups, raw meat or poultry trays, plates, or cup lids.
[0123] In some embodiments, the shaped fiber product is produced by the process of the present invention.
[0124] According to a third aspect, the present invention provides the use of a composition comprising: at least one anionic polymer having a molecular weight of at least 100 kDa; · cationic polymers; Here, the anionic polymer and cationic polymer having a molecular weight of at least 100 kDa impart to the composition a charge density in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and a charge density in the range of -0.1 to -3 meq / g, preferably -0.3 to -2.5 meq / g, more preferably -0.5 to -2.0 meq / g when measured as an aqueous solution at pH 7.0, and further In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; Some embodiments include pigments to improve the grease and oil resistance of the molded fiber.
[0125] In some embodiments, the composition is used to improve grease resistance. In some embodiments, the composition is used to improve oil resistance. In some embodiments, the composition is used to improve oil and grease resistance.
[0126] In some embodiments, polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are used in addition to the composition to improve the oil resistance of the thermoformed textile products.
[0127] In some embodiments, in addition to the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof and the composition, a pigment is used to improve the grease and oil resistance of the thermoformed textile product.
[0128] In some embodiments, in addition to the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, the composition, and the pigment, a sizing agent, fixing agent, or mixtures thereof is used to improve the grease and oil resistance of the thermoformed textile product. [Example]
[0129] Example 1 according to the present invention
[0130] First, 0.1-0.3% (dry weight) of AKD is added to a fiber raw material having a consistency of 0.3-0.5%. The fiber raw material is made from 100% birch kraft pulp. Next, 0.2-0.4% (dry weight) of polyamide epichlorohydrin (PAE) is added to the fiber raw material. Next, 0.2-0.4% (dry weight) of PDACMAC+CPAM is added to the fiber raw material. Next, 1-3% (dry weight) of a composition comprising at least one anionic polymer having a molecular weight of at least 300-500 kDa, a cationic polymer, and in some embodiments, a PAAE is added to the fiber raw material. After each agent is added to the fiber raw material, it is mixed under turbulent conditions for at least 1 minute before adding the next agent.
[0131] Example 2, Comparative Example
[0132] The same methods and chemicals as in Example 1 were used to prepare and characterize 2D molded products / sheets, but this time PAAE and cationic starch were tested alone and together, with the PAAE being added to the fiber stock first, followed by the cationic starch. Compositions containing at least one anionic polymer with a molecular weight between 300 and 500 kDa, a cationic polymer, and PAAE were tested as in Example 1. PAAE was also tested with the anionic polymer in the composition by adding the PAAE first, followed by the anionic polymer to the fiber stock.
[0133] Two-dimensional (2D) part / sheet preparation
[0134] After the chemicals described in Examples 1 and 2 are introduced into the fiber raw material, the fiber raw material is vacuum molded under a vacuum of 200-650 mBar against a forming wire with a flat circular shape of 10 cm diameter and an opening of 200-400 microns to a dryness of 20-30% using a Dynamic Drainage Analyzer (DDA). Dry weight is 200-800 g / m 2 The wet 2D molded product / sheet is hot-press dried between metal plates at 130-200 °C until it reaches 94-99% dryness, and then thermoformed to a thickness of 0.2-1.2 mm. The hot-press dried and thermoformed 2D fiber molded product / sheet is shown in Figure 6.
[0135] 2D fiber molded products are 0.5g / cm 3 ~1.5g / cm 3 , preferably 1.0 to 1.2 g / cm 3 The material can be hot pressed and / or thermoformed to a density of 0.1 to 1.2 mm, preferably 0.3 to 0.8 mm.
[0136] Three-dimensional (3D) part preparation
[0137] After the chemicals are introduced into the fiber raw material, a 3D forming wire with a suction mold is immersed into the fiber raw material, and the fiber raw material is pulled out of the 3D wire with an opening of 200-500 microns under a vacuum of up to 900 mBar to form the fiber raw material. The formed 3D molded product is pulled out of the fiber raw material and the liquid components are removed by vacuum suction assistance until the dryness of the wet molded 3D product is 33% on average. The wet molded 3D molded product is then transferred to a heated counter mold (130-200 °C), hot press dried, and thermoformed to a thickness of 0.2-1.2 mm and a final dryness of 90-96%. The dried 3D fiber molded product is shown in Figure 7.
[0138] The 3D molded product can be hot-press dried and thermoformed to a wall thickness of 0.2mm-1.2mm (e.g. 0.5mm-0.8mm), length of 5cm-50cm, width of 5cm-50cm, and depth of 2cm-20cm.
[0139] Oil and grease resistance test
[0140] The oil and fat tests were performed using the test method based on the standard ASTM F119-82:2015. The grease tests were performed using the test method based on the standard TAPPIT559:2012.
[0141] As can be seen from Figures 1 and 4, the thermoformed articles (2D molded articles / sheets) of the present invention show improved oil resistance compared to the zero test (only fiber raw materials including cellulosic fibers, no chemicals added) and the comparative thermoformed articles. As can be seen from Figures 2 and 5, the thermoformed articles (2D molded articles / sheets) of the present invention show increased dry tensile properties. As can be seen from Figure 3, the thermoformed articles (2D molded articles / sheets) of the present invention show increased humid tensile properties.
[0142] Various embodiments have been described. The terms "having", "comprising" and "including" are to be interpreted in an open-ended manner and do not exclude the presence of other elements.
[0143] The above description provides a complete and informative description of the best mode for carrying out the invention currently contemplated by the inventors using non-limiting examples of specific implementations and embodiments. However, as will be apparent to those skilled in the art, the details of the above-described embodiments do not limit the invention and may be implemented in other embodiments using equivalent means or combinations of various embodiments without departing from the characteristics of the invention.
[0144] Moreover, features of the exemplary embodiments disclosed above may be employed without the corresponding use of other features.Accordingly, the foregoing description should be considered as merely illustrative of the principles of the present invention, and not in limitation thereof.The scope of the present invention is limited only by the appended claims.
Claims
1. 1. A method for improving the grease and oil resistance of a molded textile product, comprising: Obtaining a fiber raw material comprising cellulosic fibers; introducing a composition into said fiber raw material; wherein the composition comprises at least one anionic polymer having a molecular weight of at least 100 kDa; a cationic polymer; wherein the anionic polymer and the cationic polymer impart to the composition a charge density in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and a charge density in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured in aqueous solution at pH 7.0; In some embodiments, the method includes introducing polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof, to the fiber raw material; forming the fiber raw material; A method comprising:
2. 10. The method of claim 1, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fiber raw material.
3. 3. The method according to claim 1 or 2, wherein a pigment is introduced into the fibre raw material.
4. The method according to any one of claims 1 to 3, wherein the fibrous material is formed into a sheet.
5. The method of claim 4 , wherein the sheet is formed or molded into a three-dimensional product.
6. The method according to any one of claims 1 to 3, wherein the fibrous material is formed into a three-dimensional product.
7. 4. The method according to claim 1, wherein the fibrous material is wet shaped and the wet shaped fibrous material is formed into a three-dimensional product.
8. 8. The method of any of claims 1 to 7, wherein the forming comprises wet forming, wet molding, vacuum forming, vacuum forming, extrusion forming, extrusion molding, thermoforming, dry forming, heat pressing, heat press drying, hot molding, heat press forming, thermoforming, or a combination thereof.
9. 9. The method according to claim 1, wherein the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof and the composition are introduced sequentially into the fiber raw material.
10. 9. The method according to any one of claims 1 to 8, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fiber raw material before introducing the composition into the fiber raw material.
11. 9. The method according to any one of claims 1 to 8, wherein the composition is introduced into the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or a mixture thereof being introduced into the fiber raw material.
12. 12. The method of claim 1, wherein the at least one anionic polymer and the cationic polymer are introduced sequentially into the fiber raw material.
13. 12. The method according to claim 1, wherein the at least one cationic polymer is introduced into the fiber raw material before introducing the anionic polymer.
14. 12. The method according to any of the preceding claims, wherein the at least one anionic polymer is introduced into the fibre raw material followed by the at least one cationic polymer.
15. 12. The method according to any of claims 1 to 11, wherein the at least one anionic polymer, the cationic polymer, and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch, or mixtures thereof are sequentially introduced into the fiber raw material.
16. 12. The method according to any one of claims 1 to 11, wherein the at least one anionic polymer and the cationic polymer are sequentially introduced into the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or a mixture thereof being introduced into the fiber raw material.
17. 12. The method according to any one of claims 1 to 11, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or a mixture thereof is introduced to the fiber raw material, followed by sequentially introducing the at least one anionic polymer and the cationic polymer to the fiber raw material.
18. 12. The method according to any of claims 1 to 11, wherein the at least one anionic polymer is introduced into the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or a mixture thereof, and then the cationic polymer is introduced into the fiber raw material.
19. 12. The method according to any of claims 1 to 11, wherein the cationic polymer is introduced into the fiber raw material, followed by polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or a mixture thereof, and then the at least one anionic polymer is introduced into the fiber raw material.
20. 20. The method according to any of the preceding claims, wherein the composition is introduced in an amount of 5 to 50 kg / t, preferably 10 to 40 kg / t, more preferably 20 to 30 kg / t, based on the dry weight of the fibre raw material.
21. 21. The method according to any of the preceding claims, wherein polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced in an amount of 1 to 8 kg / t, preferably 2 to 6 kg / t, more preferably 2 to 4 kg / t, based on the dry weight of the fibre raw material.
22. 22. The method according to any of the preceding claims, wherein the pH of the fibre raw material is adjusted to a pH value between 5 and 9, preferably between 7 and 8, before the composition and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fibre raw material.
23. 23. The method according to any of the preceding claims, wherein the electrical conductivity of the fibre material is adjusted to between 0.05 mS / cm and 6 mS / cm, preferably between 0.1 mS / cm and 1 mS / cm, before the composition and the polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced into the fibre material.
24. 24. The method according to any one of claims 1 to 23, wherein a sizing agent, fixing agent, wet strength agent, drainage aid or mixtures thereof is introduced to the fibrous raw material after or before the composition and polyamidoamine epichlorohydrin, glyoxalated polyacrylamide, starch or mixtures thereof are introduced to the fibrous raw material.
25. 25. The method according to any of the preceding claims, wherein a polymer having both anionic and cationic groups, preferably an amphoteric polymer and / or an interpenetrating polymer network material, is introduced into the fibre raw material, preferably instead of the composition, wherein the amphoteric polymer and / or the interpenetrating polymer network material provides the charge density.
26. A molded fiber product comprising a composition, the composition comprising: at least one anionic polymer having a molecular weight of at least 100 kDa; a cationic polymer; wherein the anionic polymer and the cationic polymer impart to the composition a charge density in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and a charge density in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured in aqueous solution at pH 7.0; In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; In some embodiments, a pigment; Including, 26. A composition produced by the method of any one of claims 1 to 25.
27. 25. The molded fiber product of claim 24, comprising a food package, a food service item, a beverage package, a merchandise package, preferably an ovenable tray, a microwaveable tray, a clamshell box, other food box, a soup cup, a raw meat and poultry tray, a plate or a cup lid.
28. Use of a composition, said composition comprising: at least one anionic polymer having a molecular weight of at least 100 kDa; a cationic polymer; wherein the anionic polymer and the cationic polymer impart to the composition a charge density in the range of 0.1 to 1.5 meq / g when measured at pH 2.8, and a charge density in the range of -0.1 to 3 meq / g, preferably -0.3 to 2.5 meq / g, more preferably -0.5 to 2.0 meq / g when measured in aqueous solution at pH 7.0; and In some embodiments, the composition comprises a polyamidoamine epichlorohydrin, a glyoxalated polyacrylamide, a starch, or a mixture thereof; In some embodiments, the composition includes a pigment to improve the grease and oil resistance of the molded textile product.